Analysis of Value Added of Fresh Organic Vegetables for The Development Supply Chain Strategy - Guritno, Adi Djoko (KnE Life Sciences, 2016)
Organic vegetables have a specific consumer, limited numbers of consumers, and higher willingness to pay than fresh non-organic vegetables. Research carried out directly on each tier supply chain from farmers (suppliers), collectors, wholesalers, middlemen (traders), and point of sales in modern trade. The research objective was to determine the distribution of the added value and classify the supply chain strategy for each type of vegetable. Results showed the greatest added value is the recipient of modern trade and traders with the greatest added value: red lettuce, chili, beans, broccoli and carrots. Keywords: organic vegetables, tier, supply chain, modern trade, value added